REVALUASI AKTIVA TETAP TERHADAP PENGHASILAN KENA PAJAK PADA WP BADAN MENGGUNAKAN APLIKASI EXCEL - Drs. Muhtarudin (LPPM STMIK BANDUNG, 2013)
This research aim to examine the influence of fixed assets revaluation on taxable income of tax agency obligation. The objective of this revaluation is so that the company could counting income and expense to be more realistic and they could reflect the ability and value of firm fairly. The extreme price fluctuation causing an unbalance situation of income and expense so that it can makes tax expense unfairly. The variables that are used in this research as follows : The dependent variable is the changes of taxable income in one year after implementation of this revaluation (ΔPKPt+1), the independent variable is the revaluation itself (net increment to the revaluation balance of fixed assets), those variables are controlled by the controlling variables which are the changes of taxable income at the implementation of the revaluation (ΔPKPt), total assets and market to book value equity. This research use survey approach of descriptive method to examines all listed company in Indonesia stock exchange which are implement the revaluation of fixed assets between 2003-2007. The statistical compulation using multiple linear regression analysis. The result of this research found that this revaluation of fixed assets had positive effect significantly to the changes of taxable income a year after implementation of the revaluation, but revaluation of fixed assets makes another factors which can reduce the taxable income. One of the factor is depreciation expense. Otherwise, there is no difference of taxable income between company that implement this revaluation and the company that doesn’t.